GINKO BILOBA L. O’SIMLIGINING BOTANIK TAVSIFI, TARQALISHI VA AHAMIYATI (Ta'limning zamonaviy transformatsiyasi, 2024)
Аннотация: Мы узнаем о значении и морфологическом строении растения гинкго билоба на ферме, где оно распространено.Annotation: We will learn about the importance and morphological structure of the ginkgo biloba plant on the farm, where it is distributed.